Severity of Menopausal Symptoms among Middle-aged Women in Selected Communities of Pokhara - Pathak, Rita; Karmacharya, Ranjita (Journal of Nursing and Health Sciences Nepal, 2024)
Introduction: Menopause is one of the most significant stages in the female reproductive life cycle. It brings several physiological and psychological changes that affect women’s lives, with 75% of women experiencing menopausal symptoms in some form. The objective of the study was to assess the Frequency and Severity of Menopausal Symptoms among Middle-Aged Women residing in Pokhara Metropolitan City. Methods: A descriptive cross-sectional study was conducted among 236 respondents aged 45-60 years. Simple random sampling technique was adopted for selecting the wards. A simple random sampling technique using the lottery method was used to select three wards. Data was collected from the eligible respondents from those households of the selected wards on first come first basis by visiting house to house. Data was collected by using a validated tool i.e Menopause Rating Scale (MRS). Data was collected from 16 December 2021 to 13 February 2022. The collected data was coded into the statistical package for Social Science (SPSS) version 16 and analyzed by using descriptive and inferential statistics to measure the frequency of the symptoms and assess the severity of the symptoms respectively. Results: Findings revealed that almost all (96.6%) of respondents had at least one menopausal symptom. The most prevalent menopausal symptom was joint and muscular discomfort (75.8%) followed by irritability (73.3%) and physical and mental exhaustion (72.4%). Regarding the severity of the symptoms, joint and muscular discomfort symptoms were reported as very severe (2.1%) the most. Likewise, in the sub-domain of menopausal symptoms a higher mean score (4.24±2.91) was found in the psychological domain. Conclusions: This study concludes that the majority of women experience joint and muscular discomfort as well as irritability during menopause. Therefore, healthcare providers should provide education on the management of physical and psychological symptoms and promote routine screening to facilitate the early identification and management of menopausal symptoms.